2015
DOI: 10.5339/qmj.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus associated encephalitis in a patient undergoing haemodialysis

Abstract: We describe an elderly gentleman with end stage renal disease on haemodialysis who presented with ophthalmic zoster infection and was discharged on oral acyclovir. He presented again a few days later with confusion and expressive dysphasia. Differential diagnosis was mainly between varicella-zoster virus (VZV) associated encephalitis versus acyclovir toxicity. Cerebrospinal fluid analysis confirmed the diagnosis of VZV associated encephalitis and the patient was treated with intravenous acyclovir and steroids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Further, immunocompromised individuals and some immunocompetent adults with varicella negative history were at high risk of developing serious clinical conditions. The most reported complications due to varicella infection in the Middle East was CNS involvements followed by skin diseases,[ 25 26 37 41 51 54 68 72 73 104 ] varicella pneumonia,[ 24 32 33 37 41 ] and gastric diseases. [ 97 ] Varicella infection is often more severe and has high complication rate in adults than in children, and childhood vaccination is the only way to protect those susceptible adults of developing serious illnesses after varicella exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, immunocompromised individuals and some immunocompetent adults with varicella negative history were at high risk of developing serious clinical conditions. The most reported complications due to varicella infection in the Middle East was CNS involvements followed by skin diseases,[ 25 26 37 41 51 54 68 72 73 104 ] varicella pneumonia,[ 24 32 33 37 41 ] and gastric diseases. [ 97 ] Varicella infection is often more severe and has high complication rate in adults than in children, and childhood vaccination is the only way to protect those susceptible adults of developing serious illnesses after varicella exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] Another case study reported the serious complications resulted from primary VZV infection in a patient undergoing hemodialysis. [ 37 ] The patient was a 70-year-old male presented with end-stage renal disease on hemodialysis; he was diagnosed for VZV encephalitis and was treated with intravenous acyclovir and steroids with full recovery back to preadmission neurological status. The study emphasized the role of varicella complications especially in immunosuppressed patients and the need for zoster vaccination in dialysis patients.…”
Section: Omanmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that patients on hemodialysis have an increased risk of varicella-zoster virus (VZV) infections compared to the general population. [ 4 ] Risk factors for cranial herpes infection include dissemination and immunosuppression. Tremors and disorientation are the most common clinical manifestations, seen in 40% of people each, while agitation and hallucinations are seen in 22 and 25% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%